Association of Language Barriers With Process Outcomes After Craniotomy for Brain Tumor. Issue 4 (22nd October 2022) - Manuel, Solmaz P.; Chia, Zer Keen; Raygor, Kunal P.; Fernández, Alicia
Abstract : BACKGROUND: Little is known about the independent association of language barriers on postoperative process outcomes after craniotomies. OBJECTIVE: To evaluate the association of limited English proficiency (LEP) with length of stay (LOS), discharge disposition, hospitalization costs, and rate of 30-day readmission after craniotomy for brain tumor. METHODS: This is a retrospective cohort study of adult patients who underwent craniotomies for brain tumor from 2015 to 2019 at a high-volume neurosurgical center. Multivariable logistic regression was used to evaluate the association of LEP with discharge disposition and 30‐day readmission. Negative binomial regression was used to evaluate the association of LEP with LOS and hospitalization cost. RESULTS: Of the 2232 patients included, 7% had LEP. LEP patients had longer LOS (median [IQR] 5 [3-8] days vs 3 [2-5] days, P < .001), higher costs of hospitalization (median [IQR] $27 000 [$21 000-$36 000] vs $23 000 [$19 000-$30 000], P < .001), and were more likely to be discharged to skilled care facilities (37% vs 21%, P < .001) compared with English proficient patients. In multivariable models, the association between LEP and longer LOS (incidence rate ratio 1.11, 95% CI 1.00-1.24), higher hospitalization costs (incidence rate ratio 1.13, 95% CI 1.05-1.20), and discharge to skilled care (OR 1.76, 95% CI 1.13-2.72) remained after adjusting for confounders. There was no difference in 30-day readmission rates by language status. CONCLUSION: LEP is an independent risk factor for extended LOS, higher hospitalization cost, and discharge to skilled care in neurosurgical patients who undergo craniotomy for brain tumor. Future research should seek to understand mediators of these observed disparities.